2020
DOI: 10.1021/acsanm.0c00717
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Ferulic Acid in Lipid Nanoparticles as Antioxidant for Skin: Mechanistic Understanding through Experiment and Molecular Simulation

Abstract: Ferulic acid, though used in formulations of skin-care and cosmetic products, suffers from the problems of poor stability and low aqueous solubility. Encapsulation into nanoparticles can be a viable route to overcome these inherent problems. In this proof-of-concept, we combine experimental studies and molecular dynamics (MD) simulations to provide insights into the underlying formation mechanism of ferulic acid-loaded lipid based nanoemulsion and nanoparticle formulations in aqueous environment. This experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Previous researchers stated that FA possessed multiple bioactivities, such as anti-bacteria ( Daglia, 2012 ), antioxidant ( Mahmoud et al, 2020 ), anti-inflammatory ( Lampiasi and Montana, 2016 ), anti-obesity ( Wang et al, 2015 ), anti-tumor ( Jinhua et al, 2018 ), and regulation of blood circulation ( Zhou et al, 2017 ). Currently, FA was widely used in industries such as food preservation ( Ou et al, 2005 ), cosmetics production ( Gupta et al, 2020 ), and medication ( Wang W. M. et al, 2018 ). A few studies demonstrated the antioxidative and growth promotional functions of FA and its derivatives in livestock, as supplement in the feed ( Li et al, 2015 ; González-Ríos et al, 2016 ; Wang et al, 2019 ), but none referred to ducks.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers stated that FA possessed multiple bioactivities, such as anti-bacteria ( Daglia, 2012 ), antioxidant ( Mahmoud et al, 2020 ), anti-inflammatory ( Lampiasi and Montana, 2016 ), anti-obesity ( Wang et al, 2015 ), anti-tumor ( Jinhua et al, 2018 ), and regulation of blood circulation ( Zhou et al, 2017 ). Currently, FA was widely used in industries such as food preservation ( Ou et al, 2005 ), cosmetics production ( Gupta et al, 2020 ), and medication ( Wang W. M. et al, 2018 ). A few studies demonstrated the antioxidative and growth promotional functions of FA and its derivatives in livestock, as supplement in the feed ( Li et al, 2015 ; González-Ríos et al, 2016 ; Wang et al, 2019 ), but none referred to ducks.…”
Section: Introductionmentioning
confidence: 99%
“…The hot nanodispersion was collected and placed on an ice bath to cool down rapidly. In a recent study, we investigated this nanoencapsulated system at molecular-level, which showed successful encapsulation of ferulic acid in the nanocapsules composed of Gelucire 50/13 39 .…”
mentioning
confidence: 99%
“…Several studies have shown that some antioxidants, such as lycopene [215], quercetin [216], curcumin [217], and astaxanthin [218] can be successfully loaded onto NLCs. Other studies revealed the successful encapsulation of resveratrol [219], idebenone [220], ferulic acid [221], and curcumin [222] on SLNs. Some of the most common techniques applied for the synthesis of SLNs and NLCs are presented in Figure 9 [209].…”
Section: Solid-lipid-based Nps and Nanostructured Lipid Carriersmentioning
confidence: 99%